METHODS OF TEACHING ENGLISH IN PEDAGOGICAL INSTITUTIONS - Mamlakat Azadovna Ruzmetova; Nargiza Faxriddinovna Kurbanova (Journals Park Publishing, 2023)
This article talks about the capacity to rapidly and effectively remember new words and terms that have been learned in a manner that urges students to think more while showing English in non-linguistic higher education organizations, just as new parts of the subject. Furthermore, the issues experienced in the discourse movement are tackled by creative techniques.
Keywords: non-philological faculty, English language, innovative methods, higher education, students, problems, memory-strengthening exercises.